Effect of Different Blended Fertilizers Formulae for the Productivity of Sesame at Bench Maji Zone, South Ethiopia - Musse, Zelalem Addis; Ambaye, Shiferaw Boke (Journal of Tropical Crop Science, 2024)
Sesame productivity in our country Ethiopia is low due to unbalanced fertilization and soil fertility degradation beyond disease and lacking using an improved variety of sesame. The experiment was conducted for two growing seasons to identify the effects of different blended fertilizer formulae applications on sesame yield and yield components at Menit Goldia. The treatments are control, nitrogen, phosphorus, sulfur and boron (NPSB) formula 1 = 46 kg.ha-1 N, 54 kg.ha-1 P,10 kg.ha-1 S, and 1.07 kg.ha-1 B; formulae 2 = 69 kg.ha-1 N,72 kg.ha-1 P,13 kg.ha-1 S, and 1.4 kg.ha-1 B, formula 3 = 92 kg.ha-1 N, 90 kg.ha-1 P, 17 kg.ha-1 S, and 1.7 kg.ha-1 B. The experiment was arranged in a randomized complete block design with three replications. The application NPSB formula resulted in the highest sesame yield and yield component as compared to the control. The economic analysis demonstrated that the maximum net benefit with the highest marginal rate of return was obtained due to the application of formula 3 as compared to control, therefore formula 3 is recommended to grow sesame at Menit Goldia and other areas with similar environment.